Cytotoxic activities and effects of atractylodin and β-eudesmol on the cell cycle arrest and apoptosis on cholangiocarcinoma cell line - Kanawut Kotawong; Wanna Chaijaroenkul; Phunuch Muhamad; Kesara Na-Bangchang (Elsevier, 2018)
Cholangiocarcinoma (CCA) is the cancer of bile duct with high mortality rate particularly in Thailand. The clinical efficacy of the standard chemotherapeutics remains unsatisfactory, and therefore, discovery and development of the new alternative drugs with high efficacy and tolerability is needed. The aim of the study was to investigate cytotoxic activity as well as the underlying mechanisms through which atractylodin and β-eudesmol exert their activities on CCA cell growth inhibition, cell cycle arrest, and cell apoptosis. Effects of the compounds on cell cytotoxicity, cell cycle arrest, and cell apoptosis were analyzed using MTT assay, BD Cycletest™ Plus DNA kit, and FITC Annexin V Apoptosis Detection Kit I, respectively. The cytotoxic activities of both compounds were concentration- and time-dependent. The IC50 [mean (SD)] of atractylodin and β-eudesmol were 41.66 (2.51) and 39.33 (1.15) μg/ml respectively. Both promoted cell cycle arrest at G1 phase, and induced cell apoptosis through activation of caspase-3/7. The highest activity was observed at 48 h of exposure. Results suggest that these mechanisms are at least in part, explain the cell cytotoxic and anti-CCA activity of atractylodin and β-eudesmol shown in vitro and in vivo models. Keywords: Cholangiocarcinoma, Atractylodin, β-Eudesmol, Cytotoxicity, Cell cycle arrest, Cell apoptosis